Venice Commission: contribution to the development of the ombudsman institution in Kazakhstan - Ashirbekova, A.Б.; Bugibay , Д.Б.; Tapakova , В.Б. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
The purpose of the article is to analyze the contribution of the European Commission for Democracy through Law of the Council of Europe (Venice Commission) to the development of the ombudsman institution in Kazakhstan. In this regard, three opinions of the Venice Commission concerning the ombudsman institution in Kazakhstan were studied such as: 1099\2022 – Opinion on the draft constitutional law “On the Commissioner for the Human Rights”; 1056\2021- Opinion on the draft law “On the Commissioner for Human Rights” ; CDL-AD (2007)020 Opinion on a possible reform of the ombudsman institution in Kazakhstan. In addition, the article outlines the role and directions of the Venice Commission for the development of democratic institutions. Along with this, the history of Kazakhstan's accession to the European Commission for Democracy through Law and the list og agreements between the Council of Eurpoe and Kazakhstan are described. Also, the current Constitutional Law “On the Commissioner for Human Rights in the Republic of Kazakhstan” dated November 5, 2022 was studied for compliance with these opinions from the Venice Commission. As a result of the scientific work, some proposals were made to the norms of the Constitutional Law “On the Commissioner for Human Rights in the Republic of Kazakhstan”.